Typical Lexical Errors in Russian Speech of Greek Students (Level A2) - N. L. Fedotova; (. Z. Stamboleva (Научный диалог, 2018)
Different approaches to the interpretation of the concept “error in speech in a non-native language” are analyzed: psychological, psycholinguistic, linguistic, methodical. The possibility to use the results of the analysis of errors in speech in a non-native language to study the processes of learning the language is proved. It is emphasized that the conclusions should be taken into account when developing a complex of productive and receptive lexical exercises. The conclusion about the impropriety of dividing errors in foreign speech to “communicatively significant and insignificant” is made. The most frequent lexical errors in the Russian speech of Greek students and deviations from the lexical norms of the Russian language are revealed. The features of the influence of errors on the nature of communication are described. The article deals with the types of lexical errors that Greek students make when mastering the system of the Russian language. The classification of lexical errors in the Russian speech of Greek students is made on the basis of two criteria: the reasons for the deviation from the lexical norm and the consequences of the deviation. Recommendations for the prevention of lexical level errors when teaching the Greeks the Russian language are given.